On quantification errors of R2* R_2^* and proton density fat fraction mapping in trabecularized bone marrow in the static dephasing regime. Issue 3 (28th April 2022) - Kronthaler, Sophia; Diefenbach, Maximilian N.; Boehm, Christof; Zamskiy, Mark; Makowski, Marcus R.; Baum, Thomas; Sollmann, Nico; Karampinos, Dimitrios C.
Abstract : Purpose: To study the effect of field inhomogeneity distributions in trabecularized bone regions on the gradient echo (GRE) signal with short TEs and to characterize quantification errors on R 2 * R_2^* and proton density fat fraction (PDFF) maps when using a water‐fat model with an exponential R 2 * R_2^* decay model at short TEs. Methods: Field distortions were simulated based on a trabecular bone micro CT dataset. Simulations were performed for different bone volume fractions (BV/TV) and for different bone‐fat composition values. A multi‐TE UTE acquisition was developed to acquire multiple UTEs with random order to minimize eddy currents. The acquisition was validated in phantoms and applied in vivo in a volunteer's ankle and knee. Chemical shift encoded MRI (CSE‐MRI) based on a Cartesian multi‐TE GRE scan was acquired in the spine of patients with metastatic bone disease. Results: Simulations showed that signal deviations from the exponential signal decay at short TEs were more prominent for a higher BV/TV. UTE multi‐TE measurements reproduced in vivo the simulation‐based predicted behavior. In regions with high BV/TV, the presence of field inhomogeneities induced an R 2 * R_2^* underestimation in trabecularized bone marrow when using CSE‐MRI at 3T with a short TE. Conclusion: R 2 * R_2^* can be underestimated when using short TEs (<2 ms at 3 T) and a water‐fat model with an exponential R 2 * R_2^* decay model in multi‐echo GRE acquisitions of trabecularized bone marrow. Abstract : Click here for author‐reader discussions